Labour Relations, Trade Unionism and Wage Administration on Employee Work Attitude in Polytechnics in Osun State - Olonade, Zaccheaus Olufunminiyi; Ibrahim, Samuel Akintunde; Awosusi, Omowumi Omojola; Omotoye, Oluwatobi Oyewumi (NIU Journal of Social Sciences, 2020)
This study examined the impact of labour relations, trade unionism and wage administration on employee work attitude in Polytechnics in Osun State. The purpose of the study was to examine if labour relations, trade unionism and wage administration significantly affected employee work attitude. Descriptive research design was used and primary data was collected through self-administered structured questionnaire. Descriptive and inferential statistics were used to analyze the data. A total of 150 randomly selected respondents from selected federal and state Polytechnics participated in the study. The researcher utilized four sets of standardized scales to make up the questionnaire viz Labour Relation Scale, Trade Unionism Scale, Wage Administration Scale and Employee Work Attitude Scale. Multiple Regression were used to test the hypotheses postulated. The hypotheses revealed that there is a joint significant relationship between Labour Relation, Trade Unionism, Wage Administration and Employees’ Work Attitude [F (3,146) = 11.019, P<.05] while labour relation showed insignificantly independent prediction of employee attitude at work in Polytechnics in Osun State (β = .129, t = .183, p>.01). Also, trade union showed insignificantly independent prediction of employee attitude at work in Polytechnics in Osun State (β = -.088, t = -.128, p>.01). Finally, wage administration was significantly and independently predict employee attitude at work in Polytechnics in Osun State (β = .356, t = -.416, p<.01). The study recommended that workers should be given the opportunity to participate in decision making so as to give them a sense of belonging and enhance their performance. Also, employees should be motivated not only in order to promote harmony between management and labour but to enhance their work performance. Lastly management need to pay salaries as and when due since this has been a major cause of industrial action in many Nigerian organizations. Keywords: Labour Relations, Trade Unionism, Wage Administration, Employee Work Attitude